2017
DOI: 10.4049/jimmunol.1601318
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Metabolism as a Novel Therapeutic Approach to Autoimmunity, Inflammation, and Transplantation

Abstract: Immune cell activation and differentiation occurs concurrently with metabolic reprogramming. This insures that activated cells generate the energy and substrates necessary to perform their specified function. Likewise, the metabolic programs amongst different cells of the immune system vary. By targeting different metabolic pathways, these differences allow for selective regulation of immune responses. Further, the relative susceptibility of cells to a metabolic inhibitor is dictated by their metabolic demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 68 publications
(107 reference statements)
1
58
0
1
Order By: Relevance
“…This suggests that specific metabolic profiles govern the phenotype of T cell subsets (Geltink et al, 2018). Importantly, previous studies indicate that interfering with intracellular metabolic pathways in immune cells represents a novel attractive therapeutic approach in inflammation (O'Neill et al, 2016;Freitag et al, 2016;Bettencourt and Powell, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that specific metabolic profiles govern the phenotype of T cell subsets (Geltink et al, 2018). Importantly, previous studies indicate that interfering with intracellular metabolic pathways in immune cells represents a novel attractive therapeutic approach in inflammation (O'Neill et al, 2016;Freitag et al, 2016;Bettencourt and Powell, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to the present understanding of the pathogenesis of ARDS, immunometabolism controls the development of inflammation in patients with sepsis-induced ARDS by regulating the function of immune cells [31]. Although, the discoveries and advances targeting immune cells as an alternative approach for ARDS therapy have been reported recently, improved outcome and decreased mortality rates in patients with sepsis-related ARDS have not been explicitly described [32,33].…”
Section: At the Genetic Level Genetic Testing Makes Facilitates The mentioning
confidence: 99%
“…15 Several studies have recently demonstrated the potential for drug repurposing in CD4+ T cell-mediated diseases. 16,17 For example, 2-deoxy-Dglucose (anticancer agent) and metformin (antidiabetic drug) were shown to reverse SLE in a mouse model. 14 However, drug repurposing, as well as drug discovery and development efforts for targeting T cell metabolism have been limited due the lack of knowledge about the key molecular targets in this context.…”
Section: Introductionmentioning
confidence: 99%